1993
DOI: 10.1104/pp.101.3.1073
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphorylases in Solanum tuberosum (IV. Purification, Tissue Localization, and Physicochemical Properties of UDP-Glucose Pyrophosphorylase)

Abstract: ~l h e enzyme UDP-glucose pyrophosphorylase (UCPase) from potato (Solanum tuberosum L. cv Norchip) tubers was purified 177-fold to near homogeneity and to a specific activity of 1099 international unitslmg of protein. l h e molecular mass of the purified enzyme was 53 k D as determined by SDS-PACE and gel filtration. lmmunological and activity assays detected UGPase at similar levels in potato stems, stolons, and tubers. Leaves and roots contained lower levels of UCPase activity and protein. LineweaverBurk plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 18 publications
8
86
1
1
Order By: Relevance
“…However, we did not observe such biphasic kinetics for pea UDP-sugar pyrophosphorylase. The V max values (81 and 106 mol/min/mg protein) of the pea enzyme for respective UTP and Glc 1-phosphate are similar to those (94 and 64 mol/min/mg, respectively, determined at 0.05-0.2 mM of substrate concentrations) of the potato enzyme (20). The V max values (145 and 164 mol/min/mg) for UDP-Glc and PP i are, however, much lower than those (890 and 827 mol/min/ mg, respectively) of the potato enzyme.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…However, we did not observe such biphasic kinetics for pea UDP-sugar pyrophosphorylase. The V max values (81 and 106 mol/min/mg protein) of the pea enzyme for respective UTP and Glc 1-phosphate are similar to those (94 and 64 mol/min/mg, respectively, determined at 0.05-0.2 mM of substrate concentrations) of the potato enzyme (20). The V max values (145 and 164 mol/min/mg) for UDP-Glc and PP i are, however, much lower than those (890 and 827 mol/min/ mg, respectively) of the potato enzyme.…”
Section: Resultsmentioning
confidence: 50%
“…The properties of the enzyme differ from those of other plant UDP-Glc pyrophosphorylases in optimal pH. The relatively low optimal pH (pH 6.5-7.5) for the pea enzyme compares with pH 8.5 (for potato enzyme) (20) and pH 8.0 -9.0 (Sorghum enzyme) (26), suggesting different intercellular and/or tissue localization of the pea enzyme. Kinetics of the enzyme also differ: biphasic substrate saturation kinetics with two different K m values for UTP and Glc 1-phosphate, which resulted from the oligomeric nature of the enzyme protein, were observed for the potato enzyme (20), while the pea enzyme gave single kinetic parameters (Table V).…”
Section: Table V Kinetics Of Udp-sugar Pyrophosphorylasementioning
confidence: 79%
See 1 more Smart Citation
“…Early studies provided correlative evidence that uridine nucleotide metabolism is regulated in parallel with changes in sucrose and starch metabolism, indicating that increased sink activity involves a coordinated increase in uridine nucleotide levels (Ross and Cole, 1968;Merlo et al, 1993;Sowokinos et al, 1993). More recent physiological studies demonstrated that the rates of sucrose breakdown and starch synthesis can be modified by altering the overall uridine nucleotide levels in response to shortterm precursor feeding to tuber discs (Loef et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although its catalatic activity in soybean nodules (Vella and Copeland, 1990) and potatoes (Sowokinos et al, 1993) does not seem to be subject to a high leve1 of fine control by cellular metabolites and ions, its in vivo activity may be regulated by the availability of substrates. In the direction of UDP-Glc formation, purified UGPase from cv Norchip potatoes exhibited biphasic kinetics for the substrates Glc-1-P and UTP.…”
mentioning
confidence: 99%